ZOLEDRONIC ACID IN METASTATIC BONE DISEASE: AN AUDIT BASED DISCUSSION - Akbar, Raza Ali; Ghosh, Sanjib Kumar; Khalil, Sajjad; Moeen-ul-Haq, Sheikh (Journal of Ayub Medical College Abbottabad, 2010)
Background: Metastatic bone disease is a common problem in patients with advanced cancer causing significant morbidity and poor quality of life. Effective and less toxic treatments, like bisphophonates, can reduce morbidity in such cases. Objectives: The objectives of this study were to determine whether Zoledronic acid was administered in accordance with current recommendations for its prescribing and to produce protocols for improved patient outcomes. Methods: The study was a retrospective audit of 39 consecutive patients with metastatic bone disease secondary to solid tumours who were treated with Zoledronic acid. The records were analysed to establish the administered dose of Zoledronic acid relative to creatinine clearance. The standards for Zoledronic acid therapy were defined from best practice guidelines. Results: The commonest diagnosis in patients receiving Zoledronic acid was carcinoma prostate 19/39 (49%) followed by carcinoma breast 11/39 (28%), gastrointestinal malignancies 4/39 (10%) and renal cell carcinoma 3/39 (8%). Indications for therapy were metastatic bone disease alone 31 (79%), hypercalcaemia alone 0/39 (0%), metastatic bone disease with hypercalcaemia 5/39 (13%), and prevention of chemotherapy induced bone loss 1/39 (3%). The dose of Zoledronic acid was appropriate to the creatinine clearance in 25/39 (64%), inappropriate in 5/39 (13%) and unclear from the notes in 9/39 (23%). Conclusions: Majority of patients received Zoledronic acid for the appropriate indications. The dose of Zoledronic acid was appropriate to serum creatinine clearance in a majority of patients. Poor documentation of data pertaining to Zoledronic acid treatment is observed which can potentially lead to major errors in prescribing. We recommend using a standard form to document each episode of therapy with Zoledronic acid. Keywords: Zoledronic Acid, Metastatic Bone Disease, Audit